Candida famata-induced fulminating cholecystitis - Paulo Sergio Ramos de Araujo; Zulma Medeiros; Fabio Lopes de Melo; Maria Amelia Maciel; Heloisa Ramos Lacerda de Melo (Revista da Sociedade Brasileira de Medicina Tropical, 2013)
Lithiasic cholecystitis is classically associated with the presence of enterobacteria, such as Escherichia coli, Enterococcus, Klebsiella, and Enterobacter, in the gallbladder. Cholecystitis associated with fungal infections is a rare event related to underlying conditions such as diabetes mellitus, steroid use, and broad-spectrum antibiotic use for prolonged periods, as well as pancreatitis and surgery of the digestive tract. Here, we present the first reported case of a gallbladder infection caused by Candida famata.